Análisis Del Manejo Cromático en Los Cuatro Principales Parques de la Ciudad de Latacunga 2021- 2022. - Chávez Díaz, Luis Jesús (2022)
The present study was carried out in Latacunga city at four main parks (Vicente León, San Francisco, La Filantropía and La Laguna), which are located at an altitude of 2769 meters above sea level. The objective of the study was to analyze chromatic management of the parks. The methodology is qualitative and quantitative, since qualitative data reflect current situation of the parks and the quantitative data provide numerical values. In order to carry out this research, the first objective was to identify the existing plant species through direct observation, classify identified species by their common name, scientific name and quantify each specie through an in situ visit, then to determine morphological characteristics of species with help of chromatic circle. From obtained data, a total of 20 plant species were identified in Vicente León Park with 615 plants, 7 colors, where green predominates with 30%; in San Francisco Park, 16 plant species were identified with 403 plants, 8 colors with green predominating with 32%; in La Filantropía Park, 23 plant species were identified with 401 plants, 8 colors with green dominating with 54%; and in La Laguna Park, 20 plant species were identified with 305 plants, 8 colors with green dominating with 47%. Reflecting that green predominates in four main city parks, this being considered a cold color produces calm, seriousness and solitude to human beings. The recovery proposals for each park are focused on recover their chromatic characteristics, improving life quality of citizens and making them more attractive to tourists.